Rapid enamel deposition on Sprague Dawley after nano calcium supplementation during pregnancy - Heriati Sitosari; Alma Linggar Jonarta; Yustina Andwi Ari Sumiwi; Tetiana Haniastuti (Majalah Kedokteran Gigi Indonesia, 2018)
Calcium is one of the most important minerals needed during hard tissue development. The preparation of this material into nano-sized particle is carried out to enhance the bioavailability and distribution of calcium in the body. Lack of calcium during odontogenesis causes defect in enamel such as hypoplasia and hypomineralization. During amelogenesis, after secretion of organic matrices, enamel mineralization will start in the presence of calcium. The objective of this study was to determine the effect of nano calcium supplementation during pregnancy on enamel development. In this study, 3-month-old female Sprague Dawley were mated and divided into three groups: nano calcium group (A), micro calcium group (B), and negative control group (C). The treatment was started on day 1 of pregnancy to day 1 after birth by intragastric administration method. The mandibles of 6 pups from each group were collected and stained with hematoxylin and eosin. Examination was conducted using microscope. Enamel deposition was measured using Optilab Image Raster® and the data collected was analyzed using t-test. Histological section of mandibular right first molar on Sprague Dawley newborn pups showed that enamel was observed on day 1 after birth but only on the group treated with nano calcium and micro calcium. Statistical analysis performed showed that the difference between the two groups was significant (p<0.05). From this study it can be concluded that the administration of nano calcium during pregnancy leads to rapid enamel deposition on Sprague Dawley pups.